PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SECARA TEMATIK MELALUI METODE MUELLER DI KELAS 1 SD NEGERI 060808 MEDAN - Tiurmaida Situmeang (JURNAL TEMATIK, 2014)
Improved Literacy Starters In Through Thematic Mueller Method In Class 1 060808 SD Negeri Medan. This study aims to improve the reading skills beginning thematically through Mueller method. This research is a class act. The subjects of this study were fifty grade I. Data collection used is the ability to read the beginning of the test, observation learning process. Observations made on any action to obtain data on student activities that develop during the learning takes place. Data analysis was descriptive nature. The results showed: 1) Learning in the first cycle in the process and the results showed improved learning outcomes with an average of 71.24, 2) in the second cycle based on learning processes and learning outcomes show an increase over the 80.22. In classical mastery level of 70% of students increased to 86%. Based on the findings it can be concluded that Mueller method can improve the ability of students to read the beginning of thematic learning and make students more enjoyable. This Mueller's method can be used to be one alternative for teachers in presenting thematic teaching beginning reading.